Investigation into the applicability and optimization of the Dutch matrix sentence test for use with cochlear implant users. - Theelen-van den Hoek, Femke L.; Houben, Rolph; Dreschler, Wouter A. (International Journal of Audiology, 2014)
Objective: Matrix sentence tests use words from a fixed word matrix to compose syntactically equivalent, but semantically unpredictable sentences. These tests are suitable for monitoring performance of cochlear implant (CI) users by repeated speech intelligibility testing. This study evaluates the Dutch matrix sentence test in CI users in quiet and in noise. It then investigates the possibility to improve the test-retest reliability for CI users by selecting subsets of sentences. Design: Repeated speech intelligibility testing was performed in quiet and in noise. The effect of sentence selection on the test-retest reliability was predicted by computer simulations and experimentally evaluated using a cross-over design. Study sample: Fifteen post-lingually deafened CI users, of which eleven participated in the cross-over study. Results: The test-retest reliability equaled 2.3 dB in quiet and 1.3 dB in noise. The simulations predicted an improvement in test-retest reliability, especially in quiet. The cross-over study did not confirm the predictions. Conclusions: The results of the study suggest that the homogeneity of the sentences is not the prime component underlying the test-retest reliability. The Dutch matrix speech material and the selected subsets of sentences were equally suitable for speech intelligibility testing in CI users.